The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.5194/bg-12-1459-2015
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen cycling in the Southern Ocean Kerguelen Plateau area: evidence for significant surface nitrification from nitrate isotopic compositions

Abstract: Abstract. This paper presents whole water column data for nitrate N, O isotopic composition for the Kerguelen Plateau area and the basin extending east of Heard Island, aiming at understanding the N-cycling in this naturally iron fertilized area that is characterized by large re-current phytoplankton blooms. The KEOPS 2 expedition (OctoberNovember 2011) took place in spring season and complements knowledge gathered during an earlier summer expedition to the same area (KEOPS 1, February-March 2005). As noted by… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 59 publications
(84 reference statements)
1
16
0
Order By: Relevance
“…This change may be related to a decrease of PN content in sinking particles due to a preferential remineralization of PN relative to POC with depth, and resulting in nitrification during the bloom period. Several authors have confirmed the significance of nitrification in the Kerguelen Plateau area, with nitrification equivalent to up to 47% of the nitrate uptake Dehairs et al, 2015;Fripiat et al, 2015). Other studies, investigating suspended particles in the subsurface ocean or particles from deep sediment traps, have generally found a more rapid remineralization of N than organic C (Boyd et al, 1999;Boyd and Trull, 2007;Schneider et al, 2003), consistent with the more labile nature of N (Gordon, 1971).…”
Section: Fluxes and Degradation Of Sinking Particlesmentioning
confidence: 88%
See 1 more Smart Citation
“…This change may be related to a decrease of PN content in sinking particles due to a preferential remineralization of PN relative to POC with depth, and resulting in nitrification during the bloom period. Several authors have confirmed the significance of nitrification in the Kerguelen Plateau area, with nitrification equivalent to up to 47% of the nitrate uptake Dehairs et al, 2015;Fripiat et al, 2015). Other studies, investigating suspended particles in the subsurface ocean or particles from deep sediment traps, have generally found a more rapid remineralization of N than organic C (Boyd et al, 1999;Boyd and Trull, 2007;Schneider et al, 2003), consistent with the more labile nature of N (Gordon, 1971).…”
Section: Fluxes and Degradation Of Sinking Particlesmentioning
confidence: 88%
“…Similarly, the NPP increased from 578 to 1064 mgC m À 2 d À 1 from E-1 to E-5 stations respectively. A highly productive station (E-4W) located closer to the Kerguelen Plateau margin was also sampled but excluded from the time series, since being nonrepresentative to trace the seasonal evolution in the less productive PF meander Dehairs et al, 2015;Planchon et al, 2015). -a station north of the PF (F-L) was sampled at mid-cruise and displayed moderate dFe concentrations in surface waters (0.26 nmol L À 1 ; Quéroué et al, 2015), the highest chlorophyll-a (3 mg L À 1 ; Lasbleiz et al, 2014) and NPP (3380 mgC m À 2 d À 1 ; Cavagna et al, 2015) levels.…”
Section: Study Areamentioning
confidence: 99%
“…The δ 18 O NO3 of NADW at 40°S (2.0‰) is too high to produce the low δ 18 O NO3 reported in the Southern Ocean AABW (1.6‰); therefore, these low signatures may be produced by remineralization processes. Recent work has identified low δ 18 O NO3 in the Kerguelen Plateau area of the Southern Ocean, which has been attributed to nitrification [ Dehairs et al , ]. This may suggest that nitrification processes may be prevalent in some regions of the Southern Ocean, causing the decreases in δ 18 O NO3 to lower values in Southern Ocean‐sourced deepwater masses [ Rafter et al , ; Dehairs et al , ].…”
Section: Discussionmentioning
confidence: 99%
“…KEOPS 1 was carried out in January–February 2005 and KEOPS 2 in October–November 2011. The data include vertical profiles of nitrate δ 15 N and δ 18 O [ Trull et al ., ; Dehairs et al ., ], mixed layer particulate nitrogen (PN) δ 15 N [ Trull et al ., , ], NO 3 − and NH 4 + uptake rates in the 100 and 0.1–0.01% PAR (photosynthetically active radiation) depth ranges [ Cavagna et al ., ; P. Raimbault, unpublished results], and 234 Th‐based particulate N (PN) export rates [ Savoye et al ., ; Planchon et al ., ]. The discussion is focused on the southeast Kerguelen Plateau because this area was studied during both the spring and late summer expeditions, allowing us to constrain the seasonal evolution of the N‐biogeochemical cycle (from October to February).…”
Section: Methodsmentioning
confidence: 99%
“…Despite high primary productivity, the seasonal nitrate (NO 3 − ) drawdown was only slightly elevated (6 µmol L −1 ) in comparison to surrounding HNLC areas (3–4 µmol L −1 ) [ Pondaven et al ., ; Nelson et al ., ]. To tackle that apparent paradox, we investigated the upper ocean seasonal nitrogen (N) cycle over the southeast Kerguelen Plateau using model and data for nitrate and ammonium concentrations and uptake rates, particulate nitrogen accumulation and export, and nitrate δ 15 N and δ 18 O [ Savoye et al ., ; Trull et al ., , ; Cavagna et al ., ; Dehairs et al ., ; Planchon et al ., ].…”
Section: Introductionmentioning
confidence: 97%